Shifting borders: Islamophobia as common ground for building pan-European right-wing unity - Hafez, Farid (Patterns of prejudice, 2014)
In recent years, Islamophobia has become a useful tool for right-wing parties to mobilize electors in many European nation-states. The general xenophobic campaigns of the 1980s have given way to Islamophobia as a specific expression of racism. It is not only the new incarnations of right-wing populist parties that are making use of Islamophobic populism, but also right-wing extremist parties, whose traditions hark back to fascist or Nazi parties. This development appears unsurprising, as Islamophobia has somehow become a kind of 'accepted racism', found not only on the margins of European societies but also at the centre. Another interesting concomitant shift is the attempt by such parties to gain wider acceptance in mainstream societies by distancing themselves from a former antisemitic profile. While the main focus on an exclusive identity politics in the frame of nation-states previously divided the far right and complicated transnational cooperation, a shared Islamophobia has the potential to be a common ground for strengthening the transnational links of right-wing parties. This shift from antisemitism to Islamophobia goes beyond European borders and enables Europe's far right to connect to Israeli parties and the far right in the United States. Hafez's article explores this thesis by analysing the European Alliance for Freedom, a pan-European alliance of far-right members of the European parliament that has brought various formerly antagonistic parties together through a common anti-Muslim programme, and is trying to become a formal European parliamentary fraction in the wake of its victory in the European elections in May 2014.